An Assessment of the Genetic Diversity in a Field Population of Phytophthora nicotianae with a Changing Race Structure - Sullivan, M J (Plant disease, 2010)
One hundred fifty-three isolates of Phytophthora nicotianae that were collected over a 4-year period from a single field were subjected to amplified fragment length polymorphism (AFLP) analysis to investigate the effect of different types of resistance in tobacco (Nicotiana tabacum) on genetic diversity in the pathogen population. No race 1 isolates were detected in the field prior to initiating the study, but the race was present in multiple plots by the end of the 4-year period. There were 102 race 0 isolates and 51 race 1 isolates characterized. Seventy-six of the 153 isolates had a unique AFLP profile, whereas the remaining 77 isolates were represented by 27 AFLP profiles shared by at least two isolates. Isolates of both races were found in both the unique and shared AFLP profile groups. Twenty-three of the AFLP profiles were detected in multiple years, indicating a clonal component to the pathogen population. Race 1 isolates that were detected over multiple years were always obtained from the same plot. No race 1 profile was found in more than one plot, confirming the hypothesis that the multiple occurrences of the race throughout the field were the result of independent events and not pathogen spread. Three identical race 0 AFLP profiles occurred in noncontiguous plots, and in each case, the plots contained the same partially resistant variety. Cluster analysis provided a high level of bootstrap support for 41 isolates in 19 clusters that grouped primarily by race and rotation treatment. Estimates of genetic diversity ranged from 0.365 to 0.831 and varied depending on tobacco cultivar planted and race. When averaged over all treatments, diversity in race 1 isolates was lower than in race 0 isolates at the end of each season. Deployment of single-gene resistance initially decreased genetic diversity of the population, but the diversity increased each year, indicating the pathogen was adapting to the host genotypes deployed in the field